Dataset of shotgun metagenomic evaluation of Sorghum bicolor rhizosphere microbiome in soils preceded by Glycine maxNCBINCBINCBINCBI - Olubukola Oluranti Babalola; Ben Jesuorsemwen Enagbonma (Data in Brief)
The dataset presents the microbial diversity, community structure, and functional potential of the rhizosphere microbiome associated with Sorghum bicolor in response to crop rotation involving a Glycine max precursor. Soil samples were collected from the rhizospheres of two Sorghum bicolor cultivars, Avenger and NS55, cultivated in soils previously used for Glycine max and cultivated in soils that have not previously been used for Glycine max cultivation, as follows: i) Sorghum bicolor Avenger (SA1, SA2, and SA3) cultivated in soils previously used for Glycine max, ii) Sorghum bicolor NS55 (SN1, SN2, and SN3) grown in soils that had been cultivated with Glycine max, iii) Sorghum bicolor Avenger (RA1, RA2, and RA3) cultivated in soils not previously used for Glycine max, iv) Sorghum bicolor NS55 (RN1, RN2, and RN3) grown in soils not previously cultivated with Glycine max. Thereafter, the shotgun sequencing was done to assess the microbial composition and functional genes from the extracted DNA. The effective metagenome after QC of the twelve samples include SA1 (99.72%), SA2 (99.50%), SA3 (99.68%), SN1 (99.75%), SN2 (99.76%), SN3 (99.70%), RA1 (99.72%), RA2 (99.77%), RN3 (99.72%), RN1 (99.67%), RN2 (99.68%), and RN3 (99.54%). Information from the metagenome sequences is accessible under the bioproject numbers PRJNA1166458 (SA1, SA2, and SA3), PRJNA1166463 (SN1, SN2, and SN3), PRJNA1166623 (RA1, RA2, and RA3), PRJNA1166627 (RN1, RN2 and RN3). Actinomycetota and Function unknown dominated the microbiomes across all cropping systems. The insights gained from this dataset hold promise for advancing sustainable agricultural practices, particularly through optimizing crop rotations, developing microbial bioinoculants, and enhancing soil health. Furthermore, the functional data and the function unknown from this dataset could enrich our understanding of microbial roles in nutrient cycling, plant growth promotion, and stress mitigation, which are critical for addressing challenges in food security and environmental sustainability.